AB0034 EARLY IMMUNIZATION AGAINST TREATMENT IS ASSOCIATED TO POOR CLINICAL RESPONSE AT 6 MONTHS AND LOW NUMBER OF TRANSITIONAL B CELLS AT BASELINE IN RHEUMATOID ARTHRITIS PATIENTS TREATED BY ADALIMUMAB. (2nd June 2020) - Lucas, C.; Rodriguez, S.; Jean, R.; Albert, J. D.; Coiffier, G.; Dumontet, E.; Tarte, K.; Amé-Thomas, P.; Perdriger, A.
Abstract : Background: Circulating anti-drug antibodies (ADAs) are detectable approximatively in 33% of adalimumab treated rheumatoid arthritis (RA) patients, often within the first 6 months of therapy 1-2 . Classically, circulating ADAs associate with their specific drugs to form immune complexes, increasing drug clearance, and by this mechanism reducing therapeutic effect 3 . B cell involvement leading to ADAs production is not yet well established. Objectives: To study early ADAs formation according to clinical response to an adalimumab therapy in RA patients and the relationship between ADAs and circulating B cell subsets. Methods: 28 RA patients and 13 healthy controls were included. Patients all presented inadequately controlled RA under conventional treatment, were naive of biotherapies, and started an adalimumab treatment at baseline (M0). Responder status was determined according to the DAS28CRP score (3.2) at 3 (M3) and 6 months (M6). ADAs plasma concentration >10pg/mL at M3 defined the immunized patient group. Circulating B cell subsets were quantified by flow cytometry at M0 and M3. Results: 11 (42.3%) patients were immunized at M3. Among them, 4 (36.4%) were responders at M6 and 7 (63.6%) were non-responders. Presence and concentration of ADAs at M3 was associated to non-responder status at M6 (p=0.043; p=0.042). Immunized patients had lower transitional B cells count at M0 compared to non-immunized patients (p=0.031). Conclusion: A high but classical proportion of RA patients developed ADAs after only 3 months of adalimumab treatment. This immunization was associated to non-responder status at M6 and to a low blood transitional B cells count at baseline. Our results suggest transitional B cells implication in RA activity and biotherapy resistance due to immunization. Low concentrations of transitional B cells could be an early biomarker of immunization process against adalimumab. References: [1]Bartelds GM et al. JAMA. 2011 [2]Moots RJ et al. PLoS ONE. 2017 [3]Van Schouwenburg PA et al. Ann Rheum Dis. 2013 Disclosure of Interests: None declared